Sun Certified Solaris 9.0 System and Network Administrator All-in-One Exam Guide - Watters, Paul A. (McGraw-Hill, 2011)
This authoritative, comprehensive reference offers complete coverage of all material on the 3 Sun Certified Solaris 9 System and Network Administrator exams